When Canteens Are Absent: Family Food Routines, Adolescents’ Autonomy, And School- Day Eating in Rural Poland - Klaudia PASKUDZKA (Communications of International Proceedings, 2025)
School- day nutrition in rural settings is a service- delivery challenge affecting human capital. Using an anonymised questionnaire from rural Polish primary schools without canteens (N=  266; ages 10– 16), this study quantifies retail substitution under missing infrastructure. A compact indicator set- second breakfast from home, school-shop purchases, exposure to lunch-type meals, meal counts (total/ hot), and demand for hot lunches- was analysed with non-parametric/exact tests (χ² with Yates/Fisher; Mann– Whitney; α= 0.05). Pupils maintain eating (≈4.18 meals/day; ≈1.76 hot meals/day), yet provisioning skews to home-packed food and on-site retail (65.4% and 56.8%), while lunch-type meals are rare (26.7%). Age, rather than gender, structures behaviour: older pupils are significantly more likely to use school shops (p< 0.05); younger pupils show higher- though not statistically conclusive- demand for hot lunches. This pattern signals a service-delivery gap with implications for nutritional quality and equity. Limitations are acknowledged.
Keywords: adolescent autonomy; school- day eating; rural schools; rural families; Poland